Ecobricks as an Educational Solution for Ecoliteracy Learning in Primary Schools - Nastika, Cica; Somantri, Mubarok; Sopandi, Wahyu (International Conference on Elementary Education, 2025)
Plastic waste management in Indonesia, especially at the elementary school level, is an important issue that requires serious attention. This study aims to examine the effectiveness of using ecobricks as an ecoliteracy learning medium in elementary schools, with a focus on improving students' knowledge, attitudes and skills towards plastic waste management. This study used a mixed method approach with a triangulation design, combining quantitative and qualitative data. Quantitative data was obtained through pretests-posttests and questionnaire to measure changes in students' knowledge and attitudes, while qualitative data was collected through activity observations and interviews with classroom teachers to gain deeper insights into the learning outcomes. The results showed a significantincrease in students' ecoliteracy knowledge and attitudes after participating in ecobrick learning. The majority of students showed increased engagement during the activities and there were positive changes in their behavior regarding plastic waste management. The implication of this study is that ecobrick-based learning can be an effective method in improving students' understanding, attitude and environmentally friendly behavior. However, there is still a need to strengthen the communication aspect and consistency of environmentally friendly behavior to ensure a sustainable impact on students.